Evaluation of Marginal Seal and Microleakage of a Sealant Modified with Silver Nanoparticles in Primary Molars: In Vitro Study - Morales-Quiroga DDS, Elisa; Martínez-Sumarán DDS, MS, Alan; Hernández-Sierra MD, MS, Juan Francisco; Pozos-Guillén DDS, PhD, Amaury (Odovtos - International Journal of Dental Sciences, 2015)
The objective of this study was to evaluate the marginal seal effectiveness and microleakage of a pit and fissure sealant containing silver nanoparticles (AgNPs). An experimental in vitro study was carried out using 40 extracted temporary molars without caries or incipient caries. These molars were divided into two groups: Group A (20 molars), to which a silver nanoparticle-containing sealant was applied, and Group B (20 molars), to which a conventional sealant was applied. The marginal seal and microleakage were evaluated. No significant differences in the marginal seal or microleakage were noted between the silver nanoparticle-containing sealant and the conventional sealant.The addition of AgNPs does not alter the adhesion or resistance of the sealant.